Effect of capital structure, company size, profitability and liquidity on company value: evidence from Indonesia manufacturing companies - Widyakto, Adhi; Widyarti, Endang Tri; Suhardjo, Yohanes; Fresiliasari, Oktavie; Karim, Abdul (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2024)
This research was conducted to determine whether PBV is influenced by capital structure, company size, profitability and liquidity. This research uses two kinds of theories: signaling theory and agency theory. The data used is secondary data from the Financial Statements of Manufacturing Industry Companies listed in the Indonesia Capital Market Directory in 2018-2021. This study used panel data with a sample of 74 from 135 companies during 2018-2021. Sampling technique using purposive sampling. The results were obtained in IDX manufacturing sector the debt equity ratio and firm size has a negative and insignificant effect on price book value. Return on equity negative and significant to price book value. Current ratio has a positive and insignificant effect on price book value. The purpose of this study also to determine the significance of the effect of debt equity ratio, firm size, return on equity and current ratio on price book value.